Correlation Between Islamic Architecture and Sustainable Architecture at the Grand Mosque & Islamic Center Sidenreng Rappang - Mustafa, Mursyid; Dollah, Aris Sakkar (Journal of Islamic Architecture, 2025)
In Islamic architecture, the embodiment of building works of art radiates from both physical and metaphysical aspects, drawing on Islamic thought concepts originating from the Al-Qur'an and Hadith. The idea of sustainable architecture is an environmentally design approach that makes use of and pays attention to the balance and resources of the environment. This research aims to examine the correlation between Islamic architecture and sustainable architecture in the Grand Mosque and the Islamic Center in Sidrap. A qualitative method was used in this study to provide descriptive data in the form of written descriptions and visual representations of the research object. Through a case study, this descriptive qualitative method was employed to analyze and compare how the two mosque buildings, the Sidrap Great Mosque and the Sidrap Islamic Center, incorporate sustainable architecture in conjunction with Islamic architecture. The research found that both the Sidrap Islamic Center Grand Mosque and the Sidrap Great Mosque have implemented sustainability aspects through their mosque designs, although improvement might be needed in some aspects to achieve a more sustainable design.